KEGAGALAN PARTAI POLITIK ISLAM : KEGAGALAN AGENDA SETTING ? - Muhammad Himawan Sutanto (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
In recent years, the failure of Islamic political parties in Indonesia has occurred as result of inability to make a good agenda setting. To solve this problem, this article highlights the importance of the pattern of political communication (including the communicator, message, media, communicant and its effects) for Islamic political parties. It must be a serious concern in arranging the agenda setting. The agenda setting must be based on the voters aspiration and rational values. By these ways, Islamic political parties will be independence from their big names (such as NU for National Awakening Party (PKB), Muhammadiyah for Mandate National Party (PAN).